PERUBAHAN KOMBINASI BISNIS: IMPLEMENTASI DAN DAMPAK PSAK 22 TERHADAP KINERJA KEUANGAN PERUSAHAAN - Silmi Humaira Harahap; Suci Ralita Lestari; Naufal Fauzan Hsb; Bana Ahmad Gautama (JURNAL FAIRNESS, 2024)
This article examines the implementation of business combination accounting before and after the implementation of PSAK 22, now known as PSAK 103 on Business Combinations, with a literature study approach. This study evaluates the effect of PSAK 22 on the company's financial performance through the analysis of Return on Assets (ROA), Return on Equity (ROE), and profit margin. Before PSAK 22, companies usually used the “pooling of interest” or “purchase method”. Analysis from previous studies shows that business combinations have a significant effect on ROA, ROE, and profit margins. While mergers and acquisitions often improve financial performance, the results vary across sectors. This article aims to serve as a reference for further research on business combinations with PSAK 22/103, and requires a wider range of case studies and more diverse variables.